OPTIMISATION OF AUTOMOBILE ANTIFREEZE COMPOSITIONS - S.G. KUREN; A.D. DIACHENKO; N.A. SOKOL; S.S. VASSEL (Advanced Engineering Research)
A quantum chemical study of the structure and stability of such antifreeze components as water and glycol has been undertaken using ab initio method in DZV basis. It is shown, that if ratio of water and glycol is optimal, decreasing of temperature leads to self-organization in the molecular level and structuring of water- spirit mixture and conversion to the solid state in low temperature (-75 оС).